Organizational Climate and Burnout: A Systematic Review of the Role of Salary, Administration, and Workplace Relationships - Anwar, Ravel; Harefa, Agusman (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
The world of work has undergone a fundamental shift, with post-pandemic phenomena such as "The Great Resignation" revealing employee burnout as a critical operational and financial challenge. Addressing burnout—a syndrome characterized by emotional exhaustion, cynicism, and professional inefficacy—has become crucial to organizational sustainability. Burnout is not an individual failure but a response to a dysfunctional Organizational Climate. This systemic approach contrasts with traditional research, which is often fragmented. While the burnout literature is extensive, research frequently operates in "silos," focusing on a single stressor (e.g., only social support or only role overload). Understanding the interaction between financial, bureaucratic, and social stressors remains limited. This article explores the roles of Salary, Administrative Burden, and Workplace Relationships in relation to burnout, using a Systematic Literature Review (SLR) analyzing a final corpus of N=50 articles (2015-2025) through thematic analysis. Findings indicate that burnout is an ecosystem failure requiring holistic intervention. Thematic analysis confirms that Salary is perceived as 'justice' and 'reward,' Administrative Burden as a cognitive 'hinderance demand,' and Workplace Relationships (especially POS and leadership) as the strongest 'protective resource.' However, the primary challenge lies in the interaction of stressors: high administrative burdens and toxic workplace relationships can demonstrably nullify the positive effects of adequate compensation.